Low-Intensity Scheduled Morning Exercise for Adolescents with a Late Chronotype: A Novel Treatment to Advance Circadian Phase?. Issue 1 (24th June 2022) - Lang, C; Richardson, C; Short, M; Gradisar, M
Abstract: Study Objectives: During adolescence, an interplay between biological and environmental factors leads to constrained sleep duration and timing. The high prevalence of sleep deprivation during this developmental period is a public health concern, given the value of restorative sleep for mental, emotional, and physical health. One of the primary contributing factors is the normative delay of the circadian rhythm. Therefore, the present study aimed to evaluate the effect of a gradually advanced morning exercise schedule (30 min shift each day) completed for 45 minutes on 5 consecutive mornings, on circadian phase and daytime functioning of adolescents with a late chronotype, compared to a sedentary control group. Methods: 18 physically inactive male adolescents aged 15-18 years spent 6 nights at the sleep laboratory. Morning procedure included either 45 min walking on a treadmill or sedentary activities in dim light. Saliva dim light melatonin onset (DLMO), evening sleepiness and daytime functioning were assessed during the first and last night of laboratory attendance. Results: The morning exercise group had significantly advanced (earlier) circadian phase (27.5 min ± 32.0), while sedentary activity resulted in a phase delay (-34.3 min ± 53.2). Morning exercise also led to higher evening sleepiness in the earlier hours of the night, but not at bedtime. Mood measures improved slightly in both study conditions. Conclusions: These findings highlight the phase advancing effect of low-intensity morning exercise among this population. Future studies are needed to test the transference of these laboratory findings to adolescents' real life.